Pengembangan Modul Bordir Komputer dengan Program WILCOM ES 2006 Mata Kuliah Embroidery Jurusan Ilmu Kesejahteraan Keluarga Fakultas Pariwisata Dan Perhotelan Universitas Negeri Padang - Aflah, Nurul; Ernawati, Ernawati; Nelmira, Weni (Journal of Home Economics and Tourism, 2017)
This research aims to produce a product media Modul Computer Embroidery withWILCOM ES 2006 Program of Embroidery lesson at IKK FPP UNP. In addition, thisresearch also aims to know advisability of validity, practicality and effectiveness media.The subject research is students of Bachelor Fashion design 2015 are taking Embroiderylesson on January-June 2017. The method which use 4D (four-D) model consist of Define,Design, Develop and Desseminate. But in this research desseminate has not use becauselimitations of researcher. Technique of accumulation data uses the questionnaire,observation and test. Analysis method used presentation data. This result is advisability ofmedia modul with 92,36% rating of validity test that included in very advisability category,87,97% rating of practicality test that included in very practical category, and the modul’seffectiveness indicates a decrease in percentage of students who score under KKM from76,2 % to 4,8% and learning outcomes of students who score on KKM is increase from23,8% to 95,2% that include in very high category. This conclusion of media ModulComputer Embroidery with WILCOM ES 2006 Program of is very advisability to use inEmbroidery lesson.Kata kunci : Learning Media, Embroidery, Embroidery Computer, WILCOM ES 2006